Сферично-симетричний Р/У всесвiт, взаємодiючий з вакуумним Б–Д скалярним полем - Singh, K. P.; Dewri, M. (Publishing house "Academperiodika", 2019)
We study a spherically symmetric vacuum cosmological model of the Universe interacting with the Brans–Dicke (B–D) scalar field in the Robertson–Walker (R/W) metric. Exact time-dependent solutions of B–D vacuum field equations are obtained in two different cases. The physical and dynamical properties of the model are discussed in detail.